Bond Price Data and Bond Market Liquidity - Sarig, Oded; Warga, Arthur (Journal of Financial and Quantitative Analysis, 1989)
This paper attempts to characterize liquidity-driven noise in the CRSP Government Bond price data set by comparing these price records to the independently collected Shearson Lehman Brothers (SLB) Bond Data Base. We argue that discrepancies between the data sets are due largely to liquidity-driven price errors, and we show that they are systematically related to certain bond characteristics. On the other hand, these discrepancies are small in magnitude and are approximately mean zero. We examine data filters based on observable bond characteristics and show that these filters can reduce the noise in price records while preserving their mean zero nature. The effects of these errors on performance evaluation are investigated by comparing results using filtered and unfiltered data.